VARIASI WAKTU PAPARAN EKSTRAK DAUN SIRIH HIJAU (Piper betle Linn.) TERHADAP KEMATIAN LALAT - Farah Ayu Aristawati; Teguh Budi Prijanto; Irmawartini (Politeknik Kesehatan Kemenkes Bandung, 2021)
Flies can act as vectors of diseases that can transmit digestive tract diseases such as cholera, myiasis, typhus, dysentery and diarrhea. There are several alternatives to fly control, one of which is chemical methods using natural ingredients, namely green betel leaf (Piper betle Linn.). The compound content of green betel leaf (Piper betle Linn.) in the form of saponins, alkaloids and flavonoids has a bitter taste and is toxic to small animals, can paralyze and kill house flies and cause wilting of nerves and damage to spiracles in insects. The purpose of this study was to determine the effect of variations in exposure time to green betel leaf extract (Piper betle Linn.) in a green light diffuser trap on fly mortality in the Kitchen of PT. X. Type of this research is an experimental research with a post test with control design. This study used variations in exposure time of 60 minutes, 75 minutes, and 90 minutes and the betel leaf extract concentration was 75%. The samples in this study were all types of flies found in PT. X. The results of this study were the total of flies that died at an exposure time of 60 minutes was 22, 75 minutes was 27, and 90 minutes was 42.The statistical test used was one way ANOVA with a sig value of 0.001 (< 0.05) so that there was an effect of variations in exposure time to green betel leaf extract (Piper betle Linn.) on fly mortality in the Kitchen of PT. Garuda Mas Universe. The most effective time is 90 minutes. The most effective extract exposure time was 90 minutes. It is advisable for the industry to apply a 75% concentration of green betel leaf extract (Piper betle Linn.) as fly control with an exposure time of 90 minutes.